Revisiting ventilator-induced lung injury: from mechanical power to immunometabolic interaction - Luo, Yuelian; Wu, Zixuan; Wu, Jinglei; You, Zijian; Chen, Yue; Wei, Xinquan; Liang, Yujie; Yang, Jiancong; Luo, Mingbo; Chen, Jie; Dai, Huijun (Frontiers in Immunology, 2026)
Ventilator-induced lung injury (VILI) occurs through the interaction of mechanical stress, immune system changes, and metabolic shifts. Models that focus mainly on pressure and volume do not fully represent this complex process. Recent work shows that mechanical power provides a way to measure energy load and its relationship to biological injury. When mechanical energy becomes excessive, it activates cellular sensing mechanisms, leads to mitochondrial dysfunction, and activates immune responses, which increases inflammation and damages tissue. This review synthesizes recent findings regarding the interplay among mechanical, immune, and metabolic factors, examining how energy transfer, cellular signaling, and shifts in metabolic function contribute to the development of ventilator-induced lung injury. New approaches using immune-modifying treatments, compounds that reduce oxidative damage (e.g., hesperidin and exogenous surfactant), and therapies using particles from stem cells offer possible directions for improved ventilation methods and protection of lung tissue.